Entre Livros e impressos, o bibliotecário nos bastidores da censura: uma abordagem indiciária do Nazismo ao Estado Novo em Belém, PA – Brasil (1930-1945) - OLIVEIRA, Alessandra Nunes de (2017)
Discusses the ways of censorship between books and printed. Investigates the historical context of the Nazi German regime censorship in print and its influence in Brazil with the New State and the Military Intervention in State of Para in the newspaper "Folha do Norte" between (1930-1945). This is a theoretical research that seeks to understand the context of the discussion on the topic of censorship on books and printed. By indicting method, sought through the interpretative clues, find the clues to the uncertainties in the library sciences, especially historical epistemology, in the context of censorship. The indication results demonstrate new approaches and prospects of studies on censorship in books and printed in historical events like ‘Bücherverbrennung’ in Nazism, evidence of censorship in the New State and in the newspaper Folha do Norte. Discussed a reflection of censorship in Librarianship and the action of professional librarians from the historical analysis. Finally, concludes that Librarianship needs to develop more theoretical and historical questions that examine the issue of censorship and its conceptions behind the scenes of professional librarian. Lacks, therefore methodological contributions more clearer to issue censorship on books and print, to hereby establish itself as emancipatory action a new hall of operation of Library and Librarian.